أثر الصمت التنظيمي في عملية اتخاذ القرار (Economic studies journal, 2022)
The study aimed to identify the impact of organizational silence on the decision-making process of employees. The researchers recognized the opinions of a sample of employees at the Misurata Medical Center (MMC). (80) employees were selected from the study population of (100) employees. A questionnaire was designed to collect the data using a descriptive analytical method. SPSS statistical program was used for data analysis process. The study concluded that there was a significant effect, at the 0.05 level, of the variable of weak support of senior management on the decision-making process. However, there was no effect of the variables of isolation and work-related concerns on the decision-making process. Therefore, senior management is required to focus more on encouraging employees to participate in decision-making process inside the institution.
Keywords: organizational silence; decision-making; poor management support; isolation, work; related concerns